Kome pripada Bosna? / To Whom Does Bosnia Belong? - Memišević, Hamza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The text is a review of the book: Review of the book Bosnia and Herzegovina and the Western Balkans - Aspects of Geopolitics and Hybrid War, by Ahmed Kico/Miralem Kapetanović, Atlantic initiative, 2019.